Access to Sulfocoumarins by Three‐Component Reaction of β‐Keto Sulfonyl Fluorides, Arynes, and DMF. Issue 27 (15th July 2022) - Huang, Yuan; Zhao, Xueyan; Chen, Dengfeng; Zheng, Yu; Luo, Jinyue; Huang, Shenlin
Abstract: Sulfonyl fluorides have found diverse applications in multiple disciplines due to their reactivity and stability. Thus, exploiting the new reactivity of sulfonyl fluorides is of high importance to Sulfur (VI) Fluoride Exchange (SuFEx) chemistry. Reported herein is a three‐component reaction of β‐keto sulfonyl fluorides, arynes and DMF for the streamline synthesis of sulfocoumarins. The reaction proceeds by trapping of the in situ generated o ‐quinone methides with β‐keto sulfonyl fluorides, followed by selective cyclization with sulfonyl fluorides. This strategy provides a new avenue to access diverse sulfocoumarins with under mild conditions. Abstract : A novel synthesis of sulfocoumarins by three‐component reaction of β‐keto sulfonyl fluorides, arynes and DMF is reported. The reaction proceeds via trapping of the in situ generated o‐quinone methides with β‐keto sulfonyl fluorides, followed by selective cyclization with sulfonyl fluorides. This strategy provides a new avenue to access diverse sulfocoumarins under mild conditions.